ANALISIS PERSEPSI DAN POTENSI PENERAPAN URBAN FARMING SEBAGAI INOVASI BUDIDAYA DI SB SIKL KUALA LUMPUR - Ulil Hanifah; Rennanti Lunnadiyah Aprilia (Nusantara Hasana Journal, 2026)
Urban farming is a cultivation innovation that is highly relevant for environments with limited land availability and can also function as a contextual learning medium in community-based educational settings, including the Sanggar Belajar (SB) of SIKL Kuala Lumpur. This study aimed to analyze perceptions and the potential implementation of urban farming as a cultivation innovation based on the views of three respondent groups: teachers/sanggar managers, parents of Grade 5 students, and Grade 5 students. The study employed a descriptive quantitative approach using a Likert-scale questionnaire (1–5). The respondents consisted of 4 teachers/sanggar managers, 7 parents, and 13 students. Data were analyzed using total scores, mean values, and the Respondent Achievement Level (TCR), and then interpreted into perception categories. The results showed that teachers/sanggar managers had a positive perception of urban farming, with a high category score (mean = 4.00; TCR = 80.00%), particularly in terms of conceptual understanding and its relevance to learning activities. Parents also demonstrated a positive perception in the high category (mean = 4.02; TCR = 80.48%), with the strongest support related to economic benefits, family access to fresh vegetables, and social cohesion. Meanwhile, students showed high to very high enthusiasm toward urban farming activities, especially in planting, caring for plants, harvesting, and feeling proud of consuming the harvest together. These findings indicate that urban farming has strong potential to be developed as a learning and community empowerment program at SB SIKL Kuala Lumpur. The main challenges are related to the availability of facilities, initial resource support, and sustained participation.